PREDICTIVE ANALYTICS AND ITS ROLE IN MAKING STRATEGIC DECISIONS IN MARKETING - Городецький, Юрій Д. (Journal of Strategic Economic Research, 2023)
The article examines the complex and multifaceted interaction between predictive analytics and strategic marketing planning. Shows how predictive analytics can transform the decision-making process and provide more accurate and efficient management of marketing resources. Covers the fundamentals of predictive analytics, including the key principles and techniques of predictive analytics and the different types of data that can be used to create predictive models, as well as the tools and technologies that support this process. By examining the role of predictive analytics in strategic marketing, you can understand how it can help you adapt to rapidly changing market conditions and improve the effectiveness of your marketing campaigns. Application of predictive analytics in a variety of industries and marketing scenarios, demonstrating its potential to improve decision-making at all levels of marketing strategy. Possible dangers and limitations associated with the use of predictive analytics in marketing are also discussed. Emphasizes the importance of taking a critical approach to interpreting the results of predictive analytics and points out the need to take into account ethical considerations, particularly regarding privacy and data protection. The final part of the article focuses on the future of predictive analytics in marketing. It examines possible areas for development in this area, such as the integration of artificial intelligence and machine learning, and discusses how these technologies can further expand the power of predictive analytics to make effective strategic decisions in marketing.